FRI0363 Children have a longer delay in diagnosis of takayasu arteritis than adolescents: lack of awareness about the disease?. (23rd January 2014) - Clemente, G.; Len, C.; Silva, C. A.; Sachetti, S.; Ferriani, V.; Sztajnbok, F.; Oliveira, S.; Bica, B.; Cavalcanti, A.; Robazzi, T.; Bandeira, M.; Hilário, M. O.; et al.
Abstract : Background: Takayasu's arteritis (TA) is a chronic granulomatous vasculitis affecting the large and medium arteries and can result in end organ damage. The disease is rare and there are few reports about the clinical features in the pediatric population. Objectives: To evaluate and to compare the clinical features of TA in Brazilian children and adolescents. Methods: In this Brazilian multicenter retrospective study including 10 pediatric rheumatology centers we identified 71 children and adolescents with TA diagnosed before the age of 18 years according to the validated classification criteria for pediatric age 1 . Patients' demographic, clinical, laboratory and angiographic data were collected. The angiographic type was classified according to the 1994 International Conference of Takayasu arteritis in Tokyo 2 . Patients were divided in 2 groups: children, younger than 10 years – group 1, and adolescents, older than or equal to 10 years – group 2 and their disease characteristics at initial presentation were compared. Results: Thirty-six (50.7%) patients were in group 1 and 35 (49.3%) were in group 2. Twenty-one (58.3%) patients in group 1 and 30 (85.7%) patients in group 2 were girls (p=0.010). The mean onset age was 5.7 and 12.7 in groups 1 and 2 (p<0.001); the mean time to diagnosis was 1.8 and 0.7 in groups 1 and 2 (p= 0.001) and the mean follow-up time was 7.2 and 3.6 in groups 1 and 2 (p <0.001). The predominant clinical symptoms at onset were decreased pulses (85.9%), followed by arterial hypertension (84.5%), constitutional (77.5%) and neurological symptoms (70.4%), however without statistical differences between the two groups. The main laboratory finding was an increased erythrocyte sedimentation rate followed by leukocytosis. Anemia and thrombocytosis were significantly more frequent in group 1 (p = 0.031; p= 0.001). Angiographic data were similar in both groups. Conclusions: Children under the age of 10 had more laboratory abnormalities, but similar clinical and angiographic features when compared to adolescents with TA. A delay in diagnosis is more common in younger patients and clinicians must be aware about this disease in this age group. References: Ozen S, Pistorio A, Iusan SM, Bakkaloglu A, Herlin T, Brik R et al. EULAR/PRINTO/PRES criteria for Henoch-Schoenlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu's arteritis: Ankara 2008. Part II: Final classification criteria. Ann Rheum Dis. 2010;69:798-806. Hata A, Noda M, Moriwaki R, Numano F. Angiographic findings of Takayasu arteritis: New classification. Int J Cardiol.1996;54(suppl):S155-S163. Disclosure of Interest : None Declared